Modification and Characterization of Some New Levofloxacin Heterocyclic Derivatives as COX-2 Enzyme Inhibitors and Evaluate Their Efficacy Pharmacokinetics by Molecular Docking and the Swiss ADME Studies - Mustafa Moaied Rabeaa; Muna Ismael Khalaf (مجلة بغداد للعلوم)
In order to predict anti-inflammatory activity against (COX-2) and expect their anticancer potential, new 1,2,4-triazole-5-thiol, Oxadiazole, and Imide derivatives were modified. Physical characteristics, 1H-NMR, 13C-NMR, FT-IR spectroscopy, and other methods were used to characterize and identify the produced compounds. The newly created compounds (1-10) were based in part on the well-known anti-inflammatory medication levofloxacin. The Swiss ADME server was used to perform computational techniques, such as ADME studies, in order to forecast the pharmacokinetics of the novel drugs. To assess the selectivity of created compounds towards the COX-2 enzyme, the results showed that all compounds met the Lipinski rule of five compounds (1-10). Higher PLP fitness values than the reference compound are predicted by docking studies for ligand interactions with COX-2 protein to bind with amino acids in the active pocket (Levofloxacin ). The polarity and lipophilicity report for tiny compounds have been predicted using a boiled egg. Predictions linked with each brain disorder as well as diet for the same chemical and physical properties and their direct translation in the design of the medication molecule have also been made.